2012
DOI: 10.1038/onc.2012.466
|View full text |Cite
|
Sign up to set email alerts
|

PKCδ-mediated phosphorylation of BAG3 at Ser187 site induces epithelial−mesenchymal transition and enhances invasiveness in thyroid cancer FRO cells

Abstract: Protein kinase C delta (PKCδ) is a serine (Ser)/threonine kinase, which regulates numerous cellular processes, including proliferation, differentiation, migration and apoptosis. In the current study, Chinese hamster ovary cells were transfected with either a constitutively activated PKCδ or a dominant negative PKCδ, phosphoprotein enrichment, two-dimensional difference gel electrophoresis and mass spectrometry was combined to globally identified candidates of PKCδ cascade. We found that Bcl-2 associated athano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 43 publications
0
36
0
Order By: Relevance
“…Enhanced FRO cell migration through phosphorylation of Bcl-2 associated athanogene 3 (BAG3) was also observed in some cases [498,499].…”
Section: Thyroidmentioning
confidence: 93%
“…Enhanced FRO cell migration through phosphorylation of Bcl-2 associated athanogene 3 (BAG3) was also observed in some cases [498,499].…”
Section: Thyroidmentioning
confidence: 93%
“…Importantly, BAG3 function and levels can also be regulated by posttranslational modification. For example, phosphorylation of Ser187 of BAG3 by protein kinase C delta (PKCΔ) leads to increased epithelial-mesenchymal transition, motility and invasiveness of cancer cells [69, 70]. Expression of exogenous Tat, a protein expressed by the HIV virus, in glioblastoma cell lines enhances BAG3 protein but not mRNA levels [71].…”
Section: Bag3 Mutants Myofibrillar Myopathy and Dilated Cardiomyopathymentioning
confidence: 99%
“…In embryonic tissues, it is reported that HMGA2 plays an important role in triggering embryonic cardiogenesis [8] and activating the self-renewal in peripheral neural system [9], by which HMGA2 modulates stem cell proliferaiton and differentiation. Most importantly, HMGA2 is demonstrated to be highly expressed in most tumors [10,11] and portends a poor prognosis for cancer patients like lung cancer [12], oral squamous cell carcinoma [13,14], and breast cancer [15]. However, it is not clear whether HMGA2 overexpression is related with the progression of EOC.…”
Section: Introductionmentioning
confidence: 96%